PROBLEMS AND INNOVATIVE METHODS OF DEVELOPING METHODOLOGICAL COMPETENCES IN FUTURE TECHNOLOGICAL EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2024)
This article is about innovative and interactive methods of teaching for future teachers of technological education studying in the higher education system, having sufficient knowledge, skills, and competences in the practical application of modern technologies, and The problem and relevance of pedagogical conditions for improving the processes related to the experience of using innovative methods and methods of teaching in university practice in the development of methodical competences of future teachers and the ways of effective organization of classes are highlighted.